You've been Trumped [videorecording (DVD)] - Baxter, Anthony; Baxter, Anthony; Trump, Donald, 1946-; Moyers, Bill D. (New Video, 2013)
In this David and Goliath story for the 21st century, a group of proud Scottish homeowners take on a celebrity tycoon. At stake is one of Britain's very last stretches of wilderness. After the Scottish government overturns its own environmental laws to give Donald Trump the green light to build a golf resort on an untouched Scottish coastline, the stage is set for an extraordinary summer of discontent, as the bulldozers spring into action.